Black-cheeked gnateater (conopophaga, Melanops, Conopophagidae): a predator of small frogs and lizards of the atlantic forest of Brazil - Schunck, Fabio; Melo, Marcos A.; Malagoli, Leo R. [UNESP] (Neotropical Ornithological Soc, Usgs Patuxent Wildlife Research Ctr, 2022)
There is only one report of predation of small vertebrates by species of the Neotropical family Conopophagidae: the capture of an anuran by a Rufous Gnateater (Conopophaga lineata). Here, we present three records of predation on small vertebrates by Black-cheeked Gnateaters (Conopophaga melanops). On December 2008 in southeastern Brazil, we found a recently dead frog (Fritziana mitus, Hemiphractidae) with lesions on its body next to an adult female Black-cheeked Gnateater captured in a mist net. Additionally, searching in two digital birding platforms we found two records of predation on an anuran and a lizard by Black-cheeked Gnateaters. All three records occurred during their reproductive period, suggesting that the prey may serve as a food resource for the young. This behavior should be better investigated in the Atlantic Forest, a region with high bird and frog diversity.
Keywords: Anuran amphibians; Curucutu; Diet; Natural History; Sao Paulo; Serra do Mar